Estereotipias motoras em indivíduos com Transtorno do Espectro Autista: estudo de uma amostra - Rampazo, Stéphanny Maria (2015)
The diagnosis of Autism Spectrum Disorder (ASD) is oriented to people with losses in areas such as communication and social interaction and by the presence of repetitive stereotyped behaviors. It is a clinical diagnosis which follows standard protocols of indirect evaluation and clinical observation (direct evaluation) in order to track signals and symptoms within the 3 areas mentioned previously and having stereotyped behaviors as a clinical indicator of this evaluation. Amongst these indicators, motors stereotypes are usually observed in people with ASD, however, there are a few Brazilian researches that consider broad clinical diversity evaluation as well as its functions, once its tools and common scales explore partially this symptomatology. The objective of this study is to show the registered results of motors stereotypes of people with ASD and discuss about possible ways of stereotypes evaluation regarding its functions and presentation. The sample was built with 22 children (age varying from 3 to 12 years old) diagnosed by Unidade de Referência em Autismo Prof° Marcos Tomanik Mercadante Irmandade Santa Casa de Misericórdia de São Paulo with ASD. The stereotype´s evaluations were based on direct and indirect behavior and tracking of ADS from data base tools: a) Brazilian version of The Behavior Problems Inventory-BPI-01; b) Brazilian version of Autism Behavior Checklist - ABC; c) Video register of Stereotypes Evaluation (RAEV). d) Experimental Functional Evaluation of Stereotype. A descriptive analysis was conducted on a case by case basis with non parametric tests and correlation with the used tools. The main conclusions of this study were: 1) the three methods of assessment, recorded the stereotypies in different relative proportions: 12 behaviors that indicate motor stereotypes at ABC were recorded in varying number of subjects in the sample (only one individual did not score), and the record of percentage relative to the total possible was 43.8%. All subjects scored at BPI-01 at least one of the 24 behaviors recorded, and the record of percentage out of the total possible was 67.4%. The direct evaluation was able to register 79 behaviors considered motor stereotypes, and therefore it was considered more effective than other methods; 2) the comparison between ABC and BPI-01 shows similar behaviors, but with slightly different questions, which led to different answers. These two questionnaires are easy to apply, the use of both is recommended because they are complementary to the registration of stereotypies. No difference was found when six similar ABC and BPI-01 records were compared; 3) You can identify the function of stereotyping for each individual from an experimental functional analysis with only a 30 minute session, divided into three situations with 10 minutes each: on demand situation (the children are requested to perform a task); attention situation (the child is praised when showing stereotypes); alone situation (free observation); 4) stereotyping may have multiple functions, i.e., stereotyped behavior can begin with a self-stimulation function, maintained by automatic reinforcement, but it can vary and serve other functions, such as obtaining social attention; 5) evaluating the function of stereotyping rather than the simple topographical record enables different, more detailed and meticulous interventions.